Gênero, religião e política: a mobilização evangélica contra os direitos reprodutivos e a atuação de Damares Alves - Coutinho, Aline Beatriz (Plura, revista de estudos de religião, 2022)
This article aims to analyze, from a gender perspective, the actions of religious-political actors regarding the fight against reproductive autonomy of women and people with a uterus in the 21st century. For this, it proposes to understand how the evangelical political actors's actions and discourses were formulated in the public and political arena in society, mainly related to the theme of abortion in this period. The focus on the Jair Bolsonaro's government from the analysis of the actions of the former minister and pastor Damares Alves and his initiatives contrary to the defense of Reproductive Rights punctuate the example of the worsening that the imbrication between religion and politics in recent years has reached in Brazil.